What was the trend of the adolescent pregnancy delivery rate at Paarl Hospital over the past 10 years (1999-2008)? - Lesch, Eugene (Stellenbosch : Stellenbosch University, 2016)
Thesis (MFamMed)--Stellenbosch University, 2011.